DAYA TERIMA DAN KANDUNGAN FE NUGGET TEMPE DENGAN SUBSTITUSI HATI AYAM DAN DAUN KELOR - Mila Kandita; Nurdiana .; Hardianti . (Jurnal Pangan dan Gizi, 2026)
According to WHO (2021), the global prevalence of anemia reaches 31.2% among women aged 15–49 years, 39.8% among children aged 6–59 months, and 24.3% across all age groups. Anemia prevention is not only carried out through iron supplementation but also by increasing dietary iron intake. One potential food product is nuggets made from chicken liver, tempe, and Moringa leaf flour. This study aimed to determine the acceptability and iron (Fe) content of tempe nuggets substituted with chicken liver and Moringa leaf flour. The research employed a Completely Randomized Design (CRD) with three treatments and two replications. The selected formulation was determined using the Exponential Comparison Method (ECM). Acceptability was analyzed using the Kruskal–Wallis test, while Fe content was measured using Atomic Absorption Spectrophotometry (AAS). The results showed significant differences in color (p=0.000), taste (p=0.000), aroma (p=0.000), and texture (p=0.000). The Fe content in F1, F2, and F3 was 2.481±0.0106 mg; 2.269±0.053 mg; and 2.105±0.106 mg, respectively. F1 was identified as the best formulation and contributed 10–20% of the daily iron requirement from snack consumption across age groups. Pregnant women in the first trimester are advised to consume one piece per day, while those in the second and third trimesters should consume 2–3 pieces. It is recommended to add ingredients that can reduce the strong aroma of Moringa leaves and minimize the off-flavor of chicken liver.